How apparel companies communicate corporate social responsibility on their websites: a longitudinal study - Gaskill-Fox, Jamie N., author; Hyllegard, Karen, advisor; Ogle, Jennifer Paff, advisor; Rouner, Donna, committee member (Colorado State University. Libraries, 2010)
Corporate social responsibility (CSR) has become an essential part of Western business practices in the last two decades, and companies are increasingly communicating about their CSR efforts on their websites. Researchers have examined website communications about the CSR practices of businesses from multiple industries, but few researchers have focused on a single industry and none to date have focused on the apparel industry exclusively. In addition, an opportunity exists for researchers to focus on the changes in communications about CSR over time. The present longitudinal study fills gaps in the existing research by examining how three apparel companies (Gap, Inc., Levi Strauss & Co., and Nike) communicated about CSR on their websites and how those communications changed from 2001 to 2009. Stakeholder theory guided the development of this study and was used as a conceptual framework for the analysis. The qualitative research method Qualitative Document Analysis (QDA) was used to examine the 2001 and 2009 websites of the selected apparel companies, and constant comparison was used as a coding strategy. The results of the analysis indicated that although the apparel companies emphasized some areas of CSR more than others on their websites, seven themes related Corporate social responsibility (CSR) has become an essential part of Western business practices in the last two decades, and companies are increasingly communicating about their CSR efforts on their websites. Researchers have examined website communications about the CSR practices of businesses from multiple industries, but few researchers have focused on a single industry and none to date have focused on the apparel industry exclusively. In addition, an opportunity exists for researchers to focus on the changes in communications about CSR over time. The present longitudinal study fills gaps in the existing research by examining how three apparel companies (Gap, Inc., Levi Strauss & Co., and Nike) communicated about CSR on their websites and how those communications changed from 2001 to 2009. Stakeholder theory guided the development of this study and was used as a conceptual framework for the analysis. The qualitative research method Qualitative Document Analysis (QDA) was used to examine the 2001 and 2009 websites of the selected apparel companies, and constant comparison was used as a coding strategy. The results of the analysis indicated that although the apparel companies emphasized some areas of CSR more than others on their websites, seven themes related to CSR were identified as common to all three companies: motivations for CSR, philanthropy, labor practices, minimizing environmental impacts, accountability, and recognitions for CSR efforts. In addition, the companies put the most emphasis on addressing the following stakeholder groups within their website communications about CSR: employees, charitable organizations and communities, the natural environment, consumers, suppliers and factory workers, activists, and youth and students. In terms of changes between 2001 and 2009, the companies generally provided greater detail and communicated more about their CSR practices in 2009 than 2001. Nike was the exception to the increase in communications about CSR in that it reduced the amount of communications relative to several of the themes from 2001 to 2009. Nike did not, however, appear to be less committed to ethical practices in 2009, rather the company appeared to change the way in which it presented communications about CSR on its website. A summary figure was developed to compare how each company's website communications about CSR represented the seven identified themes in 2001 and 2009. New insights about website communications regarding CSR in the apparel industry are presented, and implications, limitations, and suggestions for future work are discussed.
Department Head: Mary Ann Littrell.